Hubungan Pengetahuan Dan Sikap Bidan Dengan Kinerja Pelayanan Imunisasi Dasar Lengkap di Puskesmas Kabupaten Ciamis Pada Masa Pandemi Covid-19 - Mellysa Wulandari Tasripin; Annisa Devi Permata (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The Covid-19 pandemic has disrupted healthcare systems worldwide, and one of the affected healthcare services is the immunization program. People are hesitant to undergo immunization due to the fear of contracting Covid-19 when visiting healthcare facilities. Midwives have duties and authority in providing healthcare services, including complete basic immunization. This study aims to determine the relationship between the knowledge and attitudes of midwives and the performance of complete basic immunization services. This is a quantitative study with a cross-sectional approach conducted offline at the Ciamis and Cijeungjing Community Health Centers. The study involved 47 midwife respondents. The results indicate that there is a significant relationship between midwives' attitudes (0.000) and the performance of complete basic immunization, but knowledge is not significantly related to the performance of complete basic immunization services.